Protecting the Ingroup? Authoritarianism, Immigration Attitudes, and Affective Polarization - Renström, Emma A.; Bäck, Hanna; Carroll, Royce (Frontiers in Political Science, 2022)
What makes people affectively polarized? Affective polarization is based on the idea that partisanship can be a social identity leading to polarization in the form of intergroup distancing between the own party and other parties. In this article, we argue that perceived threats from an outgroup can spur affective polarization. To investigate this, we use the issue of immigration, often framed as a threat by right-wing groups, to examine whether individual-level differences influence how sensititivity to the perception of immigration as a threat. One such factor is the trait right-wing authoritarianism (RWA), which is characterized by emphasis on submission to authority and upholding norms of social order. The emphasis among individuals with this trait on protecting the ingroup from threats means that negativity toward immigration is likely to extend toward political opponents, resulting in an increase in affective polarization. Thus, we hypothesize that affective polarization is likely to increase when individuals interpret immigration as threatening, particularly for individuals who are high in RWA. We evaluate and find support for this claim using a large-scale survey performed in Sweden (N = 898). The results, showing a conditional effect of immigration attitudes on affective polarization, are consistent across three commonly used measures of affective polarization; trait ratings, a social distance measure, and feeling thermometers. Overall, our results show that it is important to consider intergroup threats and intergroup differences in the context of sensitivity to such threats when explaining affective polarization.